Upaya Administratif Pembebasan Jabatan Paska Berlakunya UU Nomor 30 Tahun 2014 Tentang Administrasi Pemerintahan : Studi Kasus Perkara Nomor 23/G/2020/PTUN-Jkt - Alamsyah, Rory (Universitas Proklamasi 45, 2021)
Law Number 30 of 2014 concerning Government Administration (UU AP) as an instrument in realizing the principles of good governance to increase public trust is not flawless, in its application, it can lead to legal uncertainty and even lead to injustice especially for the State Civil Apparatus (ASN) who was sentenced to disciplinary release from office.This research is juridical-normative research that is descriptive-analytical with a case approach, historical approach, and conceptual approach to answering how the administrative measures for exemption from ASN positions under the Statutory Regulations and Invitations and how the regulatory implications are intended for legal protection and justice for ASN.The results of the research show that the Administrative Efforts in the AP Law and Law Number 5 of 2014 concerning ASN (UU ASN) cause conflicting norms that resulting confusion and emptiness of the law for ASN who are sentenced to disciplinary Exemption from Position due to Article 33 Government Regulation Number 53 of 2010 concerning Discipline Civil Servants, disciplinary punishment is set to not be submitted administrative efforts.The condition is eliminating legal protection for ASN in obtaining certainty and justice. Suggestions from this research need to be immediately issued a new Government Regulation in accordance with the mandate of Article 129 paragraph (5) UU ASN whose arrangements are harmonized with Administrative Efforts in the Government Administration Act.